2007
DOI: 10.1016/j.ejcts.2006.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with the world's first digital drainage system. The benefits of recording air leaks with graphic representation

Abstract: The ability of the DigiVent to measure airflow and present mean values for 1, 3 and 6h proved to be very practical. The ability to save data and present curves for the entire course of treatment will be an advantage for research in the field of lung surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…They also emphasized the possibility of evidence-based algorithm for the evaluation and treatment of air-leaks. Air-flowmety within chest drainage system was invented and it could display the measurement of airleaks and pleural pressures over time (8). Clinicians could utilize objective data of air-leaks and intrapleural pressures in determining the time of removal with these systems.…”
Section: Discussionmentioning
confidence: 99%
“…They also emphasized the possibility of evidence-based algorithm for the evaluation and treatment of air-leaks. Air-flowmety within chest drainage system was invented and it could display the measurement of airleaks and pleural pressures over time (8). Clinicians could utilize objective data of air-leaks and intrapleural pressures in determining the time of removal with these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were randomly assigned (using random numbers generated by a computer) to one of the following groups: digital group (electronic measure of pleural air leak using Millicore AB DigiVent TM chest drainage system) [8] or traditional group (standard water seal pleural chamber). The chest drainage system we have used in the digital group incorporates a single use electronic sensor with two components, one to measure air flow and the other for intrapleural pressure.…”
Section: Patientsmentioning
confidence: 99%
“…The use of a DCS can reportedly reduce inter-observer variability in the management of a chest tube, as DCS provides objective evidence to inform clinical decisions about PAL; consequently, the use of a DCS is associated with a reduced duration of chest tube placement and hospital stay. [1][2][3][4][5] To date, two randomized studies have shown that DCS was superior to ACS in terms of chest tube management. 6,7) The Thopaz DCS (Medela, Baar, Switzerland) has a screen that displays instantaneous values for pleural pressure and PAL rate, allowing objective, real-time, quantitative assessment of PAL via the chest tube.…”
mentioning
confidence: 99%